The Role of Teachers as Mediators in Reducing Verbal Bullying of Minority Ethnic Students at Swabina Karya Junior High School, Medan - Ihda, Shufiatul; Siregar, Muhammad Fajar Rasyiid; Susanti, Susi; Albina, Meyniar (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2025)
This study explores the phenomenon of ethnic-based verbal bullying in a multicultural junior high school setting in Indonesia, focusing on the experiences of teachers at SMP Swasta Swabina Karya Medan. Employing a qualitative phenomenological approach, data were collected through in-depth interviews, non-participatory observations, and document analysis involving seven purposively selected participants—comprising five subject teachers, one guidance counselor, and the principal. The analysis followed Moustakas’ phenomenological procedures, enabling the identification of core themes related to teachers' mediation strategies, integration of tolerance values into pedagogy, and institutional challenges in fostering multicultural understanding. Findings reveal that verbal bullying targeting minority students significantly impacts their psychological, social, and academic well-being, often underestimated by peers as mere jest. Teachers played a pivotal role as mediators, utilizing open dialogue, promoting inclusivity, and implementing intervention programs rooted in multicultural education. These strategies were found effective in mitigating bullying incidents and enhancing interethnic harmony. The study emphasizes the importance of institutional commitment through regular educational programs on diversity, strengthened school-parent collaboration, provision of counseling services, and ongoing evaluation of anti-bullying policies. The research contributes to a deeper understanding of the complex dynamics of ethnic relations in schools and offers practical implications for educators and policymakers to build more inclusive educational environments.